PERANCANGAN TIMBANGAN DIGITAL DILENGKAPI PENGUKURAN VOLUME DAN KALKULASI TARIFJASAPENGIRIMAN BARANG BERBASIS ESP32 - Thoriq Ramadhan Al Hikmah; n/a Nurussa’adah; Rusmi Ambarwati (Jurnal Mahasiswa TEUB, 2023)
Goods delivery services are service to handle all activities necessary for thedelivery and receipt of goods intended to represent the interests of the owner of thegoods. However, currently to determine the shipping rate of goods is still usingtheconventional method, namely by first weighing the goods to find out the weight of thegoods and measuring the length, width, and height to find out the volume of the goods, then accessing the database on the computer to find the shipping rates fromone city to another. After that, do manual calculations using a calculator on the weight of goods and intercity rates to get the total freight rate. Based on the problems previously described, a tool is needed to speed up the process of setting shipping rates to be more ef ective and ef icient. In this study, the design of digital scales was carried out with the measurement of object volume and calculation of shipping rates for goods delivery services based on ESP32. Based on testing the HY-SRF05 sensor (length, width, height) using an object at a predetermined distance with a ruler incomparison, the results obtained from testing the accuracy of the HY-SRF05 sensor (length) with an error percentage of 1.11%, HY-SRF05 sensor accuracy (wide) withan error percentage of 0.55%, the accuracy of the HY-SRF05 sensor (high) withanerror percentage of 1.11%. Based on testing the HY-SRF05 sensor (length, width, height, and volume) using various boxes with dif erent dimensions compared toaruler, the accuracy of measuring objects (length, width, height, and volume) usingvarious boxes obtained an average the average percentage of the overall error is1.65%. Based on testing the load cell sensor with 5 diferent positions inthemeasurement area, the accuracy of the load cell sensor was obtained with an overall average error percentage of 11.8%, and the function of calculating the freight forwarder's service rate worked well according to predetermined specifications. Keywords: Digital Scales, Goods Delivery Services, ESP32, HY-SRF05, Load Cell